Determination of delta aminolevulinic acid levels in urine; a sensitive indicator of lead exposure in construction workers - Neelam J. Patil; Pooja V. Bhatt; Sachin A. Patharkar; Alka V. Nerurkar; Pradeep N. Surve; Kapil Bhatia (Al Ameen Medical College, 2020)
Background: Occupational exposure is a major source for lead poisoning in adults. Lead toxicity disrupts the functions of the digestive system, nervous system, respiratory system, reproductive system, etc. Lead decreases the activity of δ-aminolevulinic acid dehydratase which increases the excretion δ-aminolevulinic acid. The present study is based on this principle by which lead exposure is detected by measuring the urinary δ-ALA levels in construction workers Aim: To estimate the urinary delta aminolevulinic acid levels in construction workers as an index of lead exposure. Materials and methods: The study was done on 55construction workers of age group between 18 years and 50 years with their brief history related to lead exposure. Their urine samples were analysed for δ-ALA by Ehrlich method. Results: According to our observation, it was found that out of the 55 urine samples; 16 samples (29.09%) had urinary δ-ALA levels below reference value (<5 mg/L), while 39 samples showed increased urinary δ-ALA levels (70.91%); out of these, 32 workers (82.05%) fell in the moderate-to-high exposure level category (5 or >5 to 20 mg/L), 7 workers (17.94%) fell in the dangerous - very high exposure level category (20 or >20 to 40 mg/L). Conclusion: We conclude that there is high prevalence of lead exposure in construction workers in Mumbai, and necessary precautions need to be taken to avoid it.